Six sessions of sprint interval training improves running performance in trained athletes - Koral, J.; Oranchuk, D. J.; Herrera, R.; Millet, G. Y. (The Journal of Strength and Conditioning Research, 2018)
Sprint interval training (SIT) is gaining popularity with endurance athletes. Various studies have shown that SIT allows for similar or greater endurance, strength, and power performance improvements than traditional endurance training but demands less time and volume. One of the main limitations in SIT research is that most studies were performed in a laboratory using expensive treadmills or ergometers. The aim of this study was to assess the performance effects of a novel short-term and highly accessible training protocol based on maximal shuttle runs in the field (SIT-F). Sixteen (12 male, 4 female) trained trail runners completed a 2-week procedure consisting of 4-7 bouts of 30 seconds at maximal intensity interspersed by 4 minutes of recovery, 3 times a week. Maximal aerobic speed (MAS), time to exhaustion at 90% of MAS before test (Tmax at 90% MAS), and 3,000-m time trial (TT3000m) were evaluated before and after training. Data were analyzed using a paired samples t-test, and Cohen's (d) effect sizes were calculated. Maximal aerobic speed improved by 2.3% (p = 0.01, d = 0.22), whereas peak power (PP) and mean power (MP) increased by 2.4% (p = 0.009, d = 0.33) and 2.8% (p = 0.002, d = 0.41), respectively. TT3000m was 6% shorter (p < 0.001, d = 0.35), whereas Tmax at 90% MAS was 42% longer (p < 0.001, d = 0.74). Sprint interval training in the field significantly improved the 3,000-m run, time to exhaustion, PP, and MP in trained trail runners. Sprint interval training in the field is a time-efficient and cost-free means of improving both endurance and power performance in trained athletes.